Errors in simple tenses: a comparison of language performance between school and UiTM Kelantan students / Suryani Awang, Wan Aida Wan Hassan and Wan Nazihah Wan Mohamed - Awang, Suryani; Wan Hassan, Wan Aida; Wan Mohamed, Wan Nazihah (2006)
This study aims to compare the amount and types of errors in simple tenses and verb structure among primary school students (Year 4 and 6), secondary school students (Form 3 and 5) and UiTM Kelantan students (first and third semester students). It also aims to identify any differences in the respondents' performance after 6-month lapse. To do this, the respondents' were asked to write two essays with 6-month lapse, based on the same writing stimulus. The results indicate that there is a decrease in the amount of errors by 48.49% among the primary school students. Year 4 students made 84.5% of errors while 36.26% of errors occurred among Year 6 students. An increase amounting to 4.47% is recorded among the respondents from the Alpha groups in the secondary school but there is a reduction of 13.76% among the weaker groups, i.e the Beta groups. The amount of errors seemed to be increasing steadily among UiTM students. Looking at the differences of performance of the same respondents, the Alpha groups showed an increase in the amount of errors. However, there is a reduction among Beta group students. In addition, an increase of errors is recorded among the first semester students but an opposite results were obtained among both groups of third semester students. The results also indicate that there are similarities in the most common types of errors among all respondents in this study.